2001
DOI: 10.1590/s0104-14282001000200005
|View full text |Cite
|
Sign up to set email alerts
|

Copolimerização micelar de poli(acrilamida-g-óxido de propileno): avaliação reológica e caracterização de suas soluções

Abstract: Copolímeros graftizados de poliacrilamida e poli(óxido de propileno) (PPO) foram sintetizados via técnica de polimerização micelar. Foram investigadas as mudanças de viscosidade das suas soluções frente à variação do teor de monômero hidrófobo incorporado ao copolímero, adição de sal e de tensoativo. O maior teor de grupos hidrófobos resultou em aumento da viscosidade aparente das soluções poliméricas. A adição de sal provocou maior interação entre os grupos hidrófobos verificada pela desestabilização do siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…Whenever the copolymer is dissolved, it is not necessary that its chains have the same hydrodynamic volume than that shown in solutions of nonpurified samples. Sadicoff and coworkers,15, 16 based on a study on poly(propylene oxide) (PPO)–modified acrylamide, observed a behavior opposite to that of the present work, that is, solutions from purified copolymer had intrinsic viscosities equal or slightly superior to those of copolymers solutions prepared from a nonpurified solution. The observed discrepancy relative to the tridecyl acrylate–modified acrylamide copolymers may be explained by the fact that the hydrophobic character of the tridecyl acrylate monomer is stronger than that of PPO.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Whenever the copolymer is dissolved, it is not necessary that its chains have the same hydrodynamic volume than that shown in solutions of nonpurified samples. Sadicoff and coworkers,15, 16 based on a study on poly(propylene oxide) (PPO)–modified acrylamide, observed a behavior opposite to that of the present work, that is, solutions from purified copolymer had intrinsic viscosities equal or slightly superior to those of copolymers solutions prepared from a nonpurified solution. The observed discrepancy relative to the tridecyl acrylate–modified acrylamide copolymers may be explained by the fact that the hydrophobic character of the tridecyl acrylate monomer is stronger than that of PPO.…”
Section: Resultscontrasting
confidence: 78%
“…Solutions resulting from copolymerization appeared as transparent, homogeneous, colorless, and clear. In view of the problems for purifying and quantifying these polymers,12, 15, 16 solutions resulting from polymerization reactions were used in the rheological studies. Because all the reactions were run under constant conditions (initiator amount, temperature, and reaction time) and the hydrophobic monomer content varied within narrow limits, for purposes of the present study, it was considered that molecular weights of the obtained copolymers were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizando resultados de SADICOFF et al [16] e comparando com os espectros de infravermelho no FTIR de cada amostra foi possível identificar as bandas de absorção características da poliacrilamida com vibrações em formas de bandas de Amina, Metileno (cadeia principal) e três tipos de amida. Para esta análise foi utilizada a comparação de espectros a partir da razão de bandas (intensidade).…”
Section: Resultsunclassified